2019
DOI: 10.1073/pnas.1900266116
|View full text |Cite
|
Sign up to set email alerts
|

Role of a patatin-like phospholipase inPlasmodium falciparumgametogenesis and malaria transmission

Abstract: Transmission of Plasmodium falciparum involves a complex process that starts with the ingestion of gametocytes by female Anopheles mosquitoes during a blood meal. Activation of gametocytes in the mosquito midgut triggers “rounding up” followed by egress of both male and female gametes. Egress requires secretion of a perforin-like protein, PfPLP2, from intracellular vesicles to the periphery, which leads to destabilization of peripheral membranes. Male gametes also develop flagella, which assist in binding fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…For example, upon PbPPLP2 deletion, male gametes can disrupt the PVM normally but fail to rupture the RBC membrane, thus forming a super‐flagellum, where multiple axonemes are sheathed together by the RBC membrane (Deligianni et al, 2013; Wirth et al, 2014). A phospholipase (PfPATPL1) has been found to be important for the re‐localization of the PPLP2‐containing vesicles, thus affecting gamete egress (Singh et al, 2019). Interestingly, the male OB‐associated protein PyMiGS in P. yoelii does not affect egress or formation of flagella, but it affects exflagellation (Tachibana et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, upon PbPPLP2 deletion, male gametes can disrupt the PVM normally but fail to rupture the RBC membrane, thus forming a super‐flagellum, where multiple axonemes are sheathed together by the RBC membrane (Deligianni et al, 2013; Wirth et al, 2014). A phospholipase (PfPATPL1) has been found to be important for the re‐localization of the PPLP2‐containing vesicles, thus affecting gamete egress (Singh et al, 2019). Interestingly, the male OB‐associated protein PyMiGS in P. yoelii does not affect egress or formation of flagella, but it affects exflagellation (Tachibana et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In case of PLA2, it is an important energy source enzyme and crucial in the development of Clonorchis sinensis mediated hepatic fibrosis 61 . PLA2 has been reported its role on membrane remodelling and vesicle secretion in several organisms for example P. falciparum 62 and Leishmania amazonensis 63 . Plasmodial PLA2 involves the egress of merozoites from liver-stage schizonts 64 and merozoite invasion of red blood cells 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Such changes in phospholipid compositions have had been observed in the PNPLA1-KO lines.PNPLA1 is one of four PNPLAs identified in P. falciparum, and, to date, only for PNPLA1 functional data were collected. In a recent publication,Singh et al (2019) reported a role for PNPLA1 (termed PATPL1 in this study) in malaria transmission. In accord with our data, the authors detected PNPLA1/ PATPL1 in the cytosol of the asexual and sexual blood stages of P. falciparum.…”
mentioning
confidence: 55%